Thermal behaviour Simulation of Cylindrical Battery - Mohamad Mazlan bin Rozali; Abdul Kahar, Prof. Madya Ts. Dr. Rosmila; Mohd Alhata, Nurafiqah; Teh, Mun Hoe (Enhanced Knowledge in Sciences and Technology, 2022)
Batteries are a collection of one or more cells whose chemical reactions create a flow of electrons in a circuit. Lithium Ion Battery (LIB) is said to has high energy density level, has a long life cycle and has zero memory effect. However, the temperature, on the other hand, has a significant impact on LIB performance such as potential thermal stability difficulties. For cylindrical geometry, the study determines the thermal behavior of LIB in term of surface temperature and maximum temperature of active battery material using different material for positive electrode and charge/discharge current. From the study, LIB with LMO always show a good thermal behavior in term of surface temperature and maximum temperature of active battery material. The less charge/discharge current applied, the less temperature for surface and active battery material.